Propolis from Mount Lawu: Dose-Dependent Antioxidant and Anti-Inflammatory Effects in a Rat Model of Wound Healing - Proginova Dian Yudatama; Amru Sungkar; Ida Bagus Budhi Surya Adnyana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Chronic wounds present a significant healthcare challenge, necessitating the exploration of effective adjuvant therapies. Propolis, a natural product derived from beehives, has demonstrated antioxidant and anti-inflammatory properties. This study investigated the dose-dependent effects of Mount Lawu propolis extract on oxidative stress and inflammation in a rat model of wound healing. Methods: A completely randomized experimental design was employed using male rats (Rattus norvegicus). Granulation tissue wounds were induced, and the rats were treated with varying doses of ethanol extract of Mount Lawu propolis. Immunohistochemical analysis was performed to assess the expression of Malondialdehyde (MDA) and Interleukin-6 (IL-6) in the wound tissue. Results: The results demonstrated a significant dose-dependent decrease in MDA and IL-6 expression in the propolis-treated groups compared to the control group. The high-dose propolis group exhibited the most substantial reduction in both MDA and IL-6 levels. Conclusion: Mount Lawu propolis extract exhibits potent antioxidant and anti-inflammatory effects in a dose-dependent manner, suggesting its potential as an adjuvant therapy for chronic wound management.